2016
DOI: 10.3390/ijms17071037
|View full text |Cite
|
Sign up to set email alerts
|

The Role of p38 MAPK in the Development of Diabetic Cardiomyopathy

Abstract: Diabetic cardiomyopathy (DCM) is a major complication of diabetes that contributes to an increase in mortality. A number of mechanisms potentially explain the development of DCM including oxidative stress, inflammation and extracellular fibrosis. Mitogen-activated protein kinase (MAPK)-mediated signaling pathways are common among these pathogenic responses. Among the diverse array of kinases, extensive attention has been given to p38 MAPK due to its capacity for promoting or inhibiting the translation of targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 106 publications
1
52
0
1
Order By: Relevance
“…Previous studies have shown a connection between DCM and the mitogen-activated protein kinase (MAPK) pathway (28), so we decided to examine whether HDAC3 inhibitor could block the activation of major MAPK family members: ERK1/2, JNK, and p38 MAPK. As shown in Fig 7 and Supplementary Fig 1, phosphorylated ERK1/2, JNK and p38 MAPK protein levels were significantly increased in the hearts of OVE26 diabetic mice compared with those of WT hearts at both 3 M and 6 M time points.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown a connection between DCM and the mitogen-activated protein kinase (MAPK) pathway (28), so we decided to examine whether HDAC3 inhibitor could block the activation of major MAPK family members: ERK1/2, JNK, and p38 MAPK. As shown in Fig 7 and Supplementary Fig 1, phosphorylated ERK1/2, JNK and p38 MAPK protein levels were significantly increased in the hearts of OVE26 diabetic mice compared with those of WT hearts at both 3 M and 6 M time points.…”
Section: Resultsmentioning
confidence: 99%
“…Although p38 inhibition is no longer under clinical investigation for RA, it has generated interest for a range of disorders involving dysregulated inflammation such as multiple sclerosis (62), chronic obstructive pulmonary disorder (COPD) (63), atherosclerosis (64, 65), diabetic cardiomyopathy (66), and neuropathic pain (67, 68). Our findings argue for careful analysis of the effects of p38 inhibitors on multiple potential compensatory pathways and on the background of multiple disease-relevant contexts to understand the full effects of drugs targeting p38 in inflammation-related disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The mitogen‐activated protein kinase (MAPK) family which includes extracellular signal‐regulated protein kinases 1 and 2 (ERK1/2), c‐Jun NH2‐terminal kinase (JNK), and p38MAPK plays an important role in the regulation of a large variety of cellular processes. MAPK activation is often necessary for cardiomyocyte hypertrophy, fibrosis, and apoptosis during hyperglycemia …”
Section: Introductionmentioning
confidence: 99%